2014
DOI: 10.1002/pssb.201451021
|View full text |Cite
|
Sign up to set email alerts
|

Iron-related carrier traps near the n+p-junctions of crystalline silicon solar cells: impacts of feedstock and of the fabrication processes

Abstract: An influence of the iron content in the crystal on the formation of carrier traps in the silicon solar cells was studied. Mesastructured n þ p-junctions were formed on the surface of Cz-Si wafers after various stages of a standard solar cell fabrication process. Majority carrier traps in/near the junction volume were investigated by deep level transient spectroscopy (DLTS). The trap density correlated with the total iron content in the wafers and dropped strongly with the distance from the junctions. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…All previous CTS studies were conducted on samples prepared in laboratory conditions with MIS capacitors of relatively large areas (several mm 2 ). Recently, it was shown that standard DLTS investigation on finished devices [12][13][14] can bring new and important information about carrier traps, which cannot be obtained on samples prepared under laboratory conditions. Detection of a new type of iron-related defects (near-junction volume, NJV traps) [13] and traps related to lightinduced degradation [14] became possible only due to investigation of finished solar cell structures, without significant modification of their structure and properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All previous CTS studies were conducted on samples prepared in laboratory conditions with MIS capacitors of relatively large areas (several mm 2 ). Recently, it was shown that standard DLTS investigation on finished devices [12][13][14] can bring new and important information about carrier traps, which cannot be obtained on samples prepared under laboratory conditions. Detection of a new type of iron-related defects (near-junction volume, NJV traps) [13] and traps related to lightinduced degradation [14] became possible only due to investigation of finished solar cell structures, without significant modification of their structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that standard DLTS investigation on finished devices [12][13][14] can bring new and important information about carrier traps, which cannot be obtained on samples prepared under laboratory conditions. Detection of a new type of iron-related defects (near-junction volume, NJV traps) [13] and traps related to lightinduced degradation [14] became possible only due to investigation of finished solar cell structures, without significant modification of their structure and properties. The aim of the present work was to investigate the applicability of CTS to structures fabricated under production conditions, with real dimensions of the working elements and after application of the full cycle of production processes, including the packaging.…”
Section: Introductionmentioning
confidence: 99%